Alfred Hitchcock : the legacy of Victorianism - Cohen, Paula Marantz, 1953- (The University Press of Kentucky, 2015)
This provocative study traces Alfred Hitchcock's long directorial career from Victorianism to postmodernism. Paula Cohen considers a sampling of Hitchcock's best films -- Shadow of a Doubt, Rear Window, Vertigo, Psycho -- as well as some of his more uneven ones -- Rope, The Wrong Man, Topaz -- and makes connections between his evolution as a filmmaker and trends in the larger society. Drawing on a number of methodologies including feminism, psychoanalysis, and family systems, the author provides an insightful look at the paradox of a Victorian-style gentleman who evolved into one of the leadi.